THE DEVELOPMENT OF LOGISTICS MANAGEMENT FOR MANUFACTURING INDUSTRY IN MUMBAI - Vaidya, Abhijit (2010)
This thesis makes an attempt to illustrate the development of Logistics Management in manufacturing sector in Mumbai. Manufacturing sector in India significantly contributes in development and economical growth of the country. According to estimations made by Ministry of Micro, Small and Medium Enterprises, by 2009 SME sector contributed about 45% of manufacturing output and about 40% of total exports of the country. Mumbai being economic capital of India has great importance in business world. Mumbai itself generates about 5% of India‟s GDP and it is costliest office markets in the world. In India cost of logistics is about 13% of its GDP whereas in North America cost of logistics is about 8.7%. Hence, by reducing this tremendous cost on logistics which sums up to $20 billion, price of Indian goods can be dropped by 4.3% which will make Indian goods more competitive globally.